The genus Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in China, with description of a new species and a new record - Cao, Tong; Feng, Ji-Nian (Zootaxa, 2020)
A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) in the genus Pulvinaria Targioni Tozzetti, 1866 is recorded from Yunnan, China on Pistacia chinensis Bunge. Pulvinaria pistaciae Cao & Feng sp. n. is described and illustrated, based on adult female morphology. Pulvinaria decorata Borchsenius, 1957 is recorded for the first time from China (Henan and Shaanxi). A key to the adult females of Pulvinaria species known to occur in China is provided, and a table to show their distributions in various zoogeographical regions in China.